TSCH‐over‐LoRA: long range and reliable IPv6 multi‐hop networks for the internet of things. Issue 4 (7th May 2020) - Haubro, Martin; Orfanidis, Charalampos; Oikonomou, George; Fafoutis, Xenofon
Abstract : TSCH‐over‐LoRa is a long range and reliable IPv6 multi‐hop solution that aims at combining the reliability of TSCH (Time‐Slotted, Channel Hopping) together with the long range capabilities of LoRa. TSCH‐over‐LoRa brings mesh IPv6 networking to LoRa devices, enabling the use of standard protocols (such as RPL, UDP, and CoAP) and long range operation to TSCH/6TiSCH industrial wireless IoT networks. We design, implement, and integrate TSCH‐over‐LoRa into the TSCH/6TiSCH networking stack of the Contiki‐NG operating system and experimentally demonstrate its compatibility with higher‐level protocols and its resilience to interference.